Pengaruh Kompetensi Dan Pengembangan Karier Terhadap Kinerja Karyawan Pada PT.X - Moh. Riskaedi Febriyan; Bambang Karnain; Sugiharto Sugiharto; Rina Dewi; Achmad Daengs GS (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to: (1) determine and analyze the simultaneous influence of competency and career development on employee performance at PT. , (3) To find out and analyze which variables have a dominant influence on employee performance at PT. In this research, the type of research uses a quantitative approach, the sample is 31 people, data collection uses questionnaires and data documentation. Meanwhile, the analysis uses descriptive analysis and inferential analysis. Descriptive analysis to determine the high or low levels of the observed variables with the help of data processing using the SPSS program and inferential analysis using multiple linearity regression statistics. The research results show that: (1) Competency and career development variables simultaneously influence employee performance, because the Fcount = 24.089 > Ftable = 3.34; (2) Competency variable value tcount= 2.683 > ttable = 2.048 in sig. =0.12. there is a significant influence between competency on employee performance, (3) Career development variable value t = 2.578 > ttable = 2.048 on sig. = 0.15, there is a significant influence between career development on employee performance, (4) the competency variable has a dominant influence on employee performance, because the standard value of the competency beta coefficient = 0.440 > the standard beta coefficient of career development = 0.422.